Collaborative Strategic Reading in Vocational English Classrooms: Insights from Lecturers and Students - Windy Puspitasari Suparto; Purnamawati Mohpul; Hasrul Hasrul (Synergy Education Journal of Multidisciplinary Language and Social Sciences, 2026)
Reading activities in vocational English classrooms often require students to comprehend texts related to academic study and future professional practice. In such contexts, learners frequently encounter difficulties in understanding written English, particularly when instruction relies on teacher-centred approaches. This research explored the classroom use of Collaborative Strategic Reading (CSR) in English instruction at Makassar Tourism Polytechnic, with particular attention to how the strategy was implemented and how it was experienced by both lecturers and students. A qualitative descriptive approach was employed, involving English lecturers and fifth-semester students who participated in collaborative reading activities. Data were obtained through classroom observations, semi-structured interviews, and analysis of instructional documents, then examined through thematic interpretation. The results indicate that CSR was applied through structured reading stages that encouraged interaction and shared responsibility among students. Lecturers guided the learning process by facilitating discussion rather than providing direct explanations, while students became more actively involved in negotiating meaning, clarifying vocabulary, and reflecting on text content. Students reported greater confidence and engagement during reading sessions, particularly when working collaboratively with peers. The study concludes that CSR supports a more participatory and supportive reading environment in vocational EFL classrooms and can be considered a practical instructional approach for improving students’ reading experiences in similar educational settings.